2022
DOI: 10.53560/ppasb(59-4)811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Chemical Properties for Monitoring and Maintenance of Soil Fertility in Probolinggo, Indonesia

Abstract: Soil is paramount to sustaining living in biomass production, water quality control, climatic mitigation, and biodiversity endurance. Closely associated with sustainable agriculture, it degrades soil in the long run, robbing the soil of its production capacity and food-generating ability. In Probolinggo, a regency in Indonesia, intensifying the use of chemical fertilizers and pesticides yet a declining trend in yield production was discovered. This research analyzed the acid, nitrogen, organic carbon, and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Table 1 shows that based on the Indonesian Soil Research Center, Bogor, the soil in the research area is categorized as low fertility and very low in nutrients N, P, K, and C organic [17,18]. However, C-organic in non-mining is classified as high.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows that based on the Indonesian Soil Research Center, Bogor, the soil in the research area is categorized as low fertility and very low in nutrients N, P, K, and C organic [17,18]. However, C-organic in non-mining is classified as high.…”
Section: Resultsmentioning
confidence: 99%
“…This research was carried out on land with low fertility [35,7], as shown in Chapter 2. In future research, the application of PGPR should be combined with organic fertilizer.…”
Section: Future Researchmentioning
confidence: 99%
“…PGPR requires standard soil organic content to be efficient and effective (Adinurani et al, 2021;Ekawati, 2019;Goenadi et al 2021;Medina and Azcón, 2012;Muhammad et al 2021). It takes real action and collaboration between various stakeholders so that all organic waste -agricultural waste, livestock waste, kitchen waste, leftover food, and human excrement from pit latrines and septic tanks (Abdullah et al 2020, Anukam andNyamukamba, 2022;Manzoor et al, 2020;Prasetyo et al, 2022aand b, Setyobudi et al 2021, Somorin, 2020Susanto et al, 2020) can return to agricultural lands to maintain and increase soil fertility.…”
Section: Purification Bacterial Morphology and Bacterial Physiology Testmentioning
confidence: 99%
“…In general, dry land in Indonesia is degraded due to erosion. Land degradation causes dryland organic matter to be at the lowest level (Goenadi et al, 2021;Prasetyo et al, 2022a;Purbajanti et al, 2016;Vincevica-Gaile et al, 2021). Rhizosphere bacteria are soil microorganisms that can establish a relationship with the physical and chemical conditions of the soil (Ekawati, 2019;Sukmawati et al 2021;Xiong et al 2021).…”
Section: Introductionmentioning
confidence: 99%